The role of value management in achieving best value in public sector service delivery in South Africa: a research agenda - Bowen, Paul; Pearl, Rob; Cattell, Keith; Hunter, Kirsty; Kelly, John (University of the Free State, 2007)
It is common cause that, for the most part, public sector service delivery in South Africa is in a state of disarray. Problems associated with service delivery include shortages of skilled staff, under-spending of budgets, corruption, and a general lack of capacity. Best value in public service delivery is clearly not being achieved. Best Value is an emerging initiative that aims to improve the quality of public services. The basic premise of the Best Value initiative is that the public service should procure services on the basis of value for money rather than on lowest cost. The literature suggests the use of value management with risk management within a project management framework to achieve value for money. This article outlines a research agenda for examining the role of value management in achieving best value in public sector service delivery in South Africa.

Dit is algemene kennis dat die grootste deel van dienslewering in die openbare sektor in Suid-Afrika in wanorde is. Probleme verantwoordelik daarvoor sluit in: personeel tekorte, onderbesteding van begrotings, korrupsie, en ’n algemene tekort aan bekwaamheid. Bestewaarde in dienslewering is nie bereik nie. Bestewaarde is ’n noodsaaklike inisiatief wat daarop gemik is om die kwaliteit van openbare dienste te verbeter. Die basiese doel van die bestewaarde inisiatief is dat openbare dienslewering diense moet verskaf op die basis van waarde vir geld eerder as op die laagste koste. Literatuur stel voor dat waardebestuur met risikobestuur binne ’n projekbestuurraamwerk gedoen word om waarde vir geld te kry. Hierdie artikel gee ’n navorsingsagenda om die rol van waardebestuur in die bereiking van bestewaarde in openbare dienslewering in Suid-Afrika te evalueer.
Keywords: Public sector; Service delivery; Value management; Best value; South Africa